KUMPULAN SOAL BUKU AJAR PLUSPUNKT DEUTSCH SEBAGAI LATIHAN TAMBAHAN KETERAMPILAN MEMBACA BAHASA JERMAN UNTUK SMA KELAS XI SEMESTER II - Aprianti, Ratih (LATERNE, 2017)
In learning a foreign language, the skills of reading is a skill that must be mastered by students. Learner is expected to understand the different types of readings and a series of text that they meet. One of the means of learning German is a textbook. The textbook plays a great role for teachers as well as for learners. For this reason, an analysis is needed in the German language book, namely Pluspunkt Deutsch. In this textbook there are many exercises that increase the learning process. According to Hans – Jürgen Krumm (in Kast and Neuner), exercise is an aspect that can be analyzed by the textbook. The title of this research is